2009
DOI: 10.1371/journal.pone.0004606
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Rescue of Brain Defects Induced by Overexpression of DYRK1A

Abstract: Individuals with partial HSA21 trisomies and mice with partial MMU16 trisomies containing an extra copy of the DYRK1A gene present various alterations in brain morphogenesis. They present also learning impairments modeling those encountered in Down syndrome. Previous MRI and histological analyses of a transgenic mice generated using a human YAC construct that contains five genes including DYRK1A reveal that DYRK1A is involved, during development, in the control of brain volume and cell density of specific brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 48 publications
7
144
1
2
Order By: Relevance
“…L'étude de la physiopathologie de la trisomie 21 a, quant à elle, permis de jeter les bases d'une meilleure prévention tertiaire, voire d'envisager des cibles thérapeutiques pour cette affection. Plusieurs articles récents font état de succès de stratégies thérapeutiques appliquées aux modèles animaux [48][49][50]. Enfin, il convient de souligner ici que ces travaux sur l'étiopathogénie de la trisomie 21 pourraient bénéficier à l'ensemble des maladies génétiques.…”
Section: Resultsunclassified
“…L'étude de la physiopathologie de la trisomie 21 a, quant à elle, permis de jeter les bases d'une meilleure prévention tertiaire, voire d'envisager des cibles thérapeutiques pour cette affection. Plusieurs articles récents font état de succès de stratégies thérapeutiques appliquées aux modèles animaux [48][49][50]. Enfin, il convient de souligner ici que ces travaux sur l'étiopathogénie de la trisomie 21 pourraient bénéficier à l'ensemble des maladies génétiques.…”
Section: Resultsunclassified
“…In the first experiment, mice were treated with a high dose of EGCG (30 mg/kg/day), and in 381 the second experiment they received a lower dose (9 mg/kg/day). Since EGCG crosses the placenta and 382 reaches the embryo 48 , the treatment was administered prenatally at embryonic day 9 (E9) to optimize 383 . CC-BY-NC 4.0 International license It is made available under a (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Modulating a Multisystem Circuit To Minimize Developmental Amentioning
confidence: 99%
“…In fact, gene therapy applied to the TgDyrk1A mouse model has shown that normalization of Dyrk1A gene expression was able to attenuate behavioural phenotypes, restore motor-coordination and improve sensorimotor gating (Ortiz-Abalia et al, 2008). Moreover, modulation of DYRK1A activity with the use of epigallocatechin gallate (EGCG), found in great amounts in green tea leaves, has proved successful in reverting DYRK1A-induced synaptic vesicle endocytosis defects in cultured hippocampal neurons (Kim et al, 2010) and rescuing the major phenotypic features of DYRK1A transgenic mice (Guedj et al, 2009). Following these positive outcomes, a human clinical trial has been recently completed, although no results have been published so far (NCT01394796).…”
Section: Down Syndromementioning
confidence: 99%